DOES INTRINSIC RELIGIOSITY MODERATE BETWEEN THE SELF-ASSESSMENT SYSTEM AND TAX EVASION? A RESEARCH-BASED ON GENDER - Alfriadi Dwi Atmoko (Universitas PGRI Madiun, 2021)
ABSTRACTThis study aims to examine the effect of the self-assessment system on tax evasion and the effect of intrinsic religiosity moderation on the relationship between the self-assessment system and tax evasion. This study also differences in the influence of gender on the effect of the self-assessment system on tax evasion. This research method uses moderated regression analysis (MRA) and an independent sample t-test. The results show that the self-assessment system had a negative effect on tax evasion. Meanwhile, intrinsic religiosity does not moderate the relationship between the self-assessment system and tax evasion. There are no gender differences at the level of the self-assessment system, intrinsic religiosity, and tax evasion.ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh self-assessment system terhadap tax evasion dan efek moderasi religius intrinsik pada hubungan self-assessment system dengan tax evasion. Penelitian ini juga menganalisis perbedaan gender pada tingkat self-assessment system, religius intrinsik dan tax evasion. Metode penelitian ini menggunakan analisis moderated regression analysis (MRA) dan independent sample t-test. Hasil penelitian menunjukkan bahwa self-assessment system berpengaruh negatif terhadap tax evasion. Religius intrinsik tidak memoderasi hubungan self-ssessment system dengan tax evasion. Tidak terdapat perbedaan gender pada tingkat self-assessment system, religius intrinsik dan tax evasion.